Fossil carabids from Baltic amber—III—Tarsitachys bilobus Erwin, 1971 an interesting fossil ground beetle from Baltic amber (Coleoptera: Carabidae: Trechinae): Redescription and comments on its taxonomic placement - Ortuño, Vicente M.; Arillo, Antonio (Zootaxa, 2015)
Tarsitachys bilobus (Coleoptera, Carabidae) is a fossil species described by Erwin from Baltic amber. Its description was based on only one known specimen, and thus, part of its anatomical structures were unknown as they were poorly preserved in the Holotype. In this paper we complete the description with a second specimen. A new placement among Tachyina and a new status for the genus are proposed.